Modelling microbial transport in simulated low-grade heap bioleaching systems: The hydrodynamic dispersion model. (23rd November 2017) - Govender-Opitz, Elaine; Kotsiopoulos, Athanasios; Bryan, Christopher G.; Harrison, Susan T.L.
Highlights: Microbial concentration gradient and substrate availability drives transport. Bulk advection-dispersion forces facilitates chemical and microbial transport. Integration of population balance model improved estimation of mineral leach rates. Ore-associated maximum specific growth rate significantly greater than that in PLS. Successfully predicted changes in microbial concentration in phases within ore bed. Abstract: The hydrodynamic model was developed to describe microbial growth kinetics within heap bioleaching systems. Microbial partitioning between the bulk flowing pregnant leach solution (PLS) and ore-associated phases that exist within the low-grade chalcopyrite ore bed, as a function of microbial transport between these identified phases, was investigated. Microbial transport between the bulk flowing PLS and ore-associated phases was postulated to be driven by the microbial concentration gradient between the phases, with advection and dispersion forces facilitating microbial colonisation of, and transport through, the ore bed. The population balance model (PBM) was incorporated into the hydrodynamic model to estimate mineral dissolution rates as a function of available surface area appropriately. Temporal and spatial variations in microbial concentration in the PLS and ore-associated phases are presented together with model predictions for overall ferrous and ferric iron concentrations, which account for iron concentrations in the bulk flowing PLS and that in the vicinity of the mineral surface. The model predictions for PLS and ore-associated microbial concentrations are validated with experimental data, demonstrating the improvement of this model over the previously presented 'biomass model'. Based on Michaelis-Menten type kinetics, model-predicted true maximum specific growth rates for Acidithiobacillus ferrooxidans in the PLS and ore-associated phases were found to be 0.0004 and 0.019 h −1, respectively. Estimated microbial attachment and detachment rates suggest that microbial growth is more prolific in the ore-associated phases with subsequent transport to the bulk flowing PLS. Sensitivity analysis of the hydrodynamic transport model to changes in the advection mass transfer coefficient, dispersion coefficient and inoculum size are discussed. For the current reactor configuration, increasing the irrigation rate from 2 to 2.5 L m −2 h −1, i.e. increasing the advection mass transfer rate, resulted in a significant decrease in microbial retention within the ore bed.